Performance Controlling of Village Apparatus Based on Quality Management at the Mulya Agung Village Office Musi Banyuasin Regency - Amilda; Tri Septya Rohmah; Ibrahim (Universitas Pendidikan Mandalika, 2025)
This study aims to analyze the implementation of performance controlling of village officials based on quality management at the Mulya Agung Village Office, Lalan Subdistrict, Musi Banyuasin Regency. It examines the standard-setting process, the implementation of activities in controlling the performance of village officials based on quality management, compares actual performance with predetermined criteria, and explores ways to address problems in controlling the performance of village officials at the Mulya Agung Village Office. This research uses a qualitative method through field-based approaches, primarily using interviews. Data collection techniques include observation, interviews, and documentation. Data processing and analysis are carried out in three stages: data reduction, data presentation, and drawing conclusions. The informants in this study consist of the village head, village officials, the village consultative body, and local community members. The validity of the data was tested using triangulation, including source and technique triangulation. The results of the study indicate that the performance controlling of village officials at the Mulya Agung Village Office has been running well, as shown by the implementation of controlling in accordance with the applicable rules and regulations. For instance, when addressing performance-related issues among village officials or employees, the village head, together with all stakeholders, holds joint meetings or deliberations. These meetings help produce solutions that increase compliance and discipline among stakeholders, raise awareness among those facing issues, and serve as valuable lessons for the future. Keywords: Controlling, Village Officials’ Performance, Quality Management